The Role of Training in Increasing the Productivity of Tempe Sanan Chips MSMEs through Social Capital: A Perspective of the Creative Economy Ecosystem - Benita Rachmania; Yuyuk Liana (Institut Teknologi dan Bisnis Asia Malang, 2026)
This study is to analyze the effect of training on the productivity of tempeh chips MSMEs in the Malang City Sanan Center and the role of social capital as a mediating variable. Using a quantitative approach with an explanatory research design on 83 MSME actors selected through simple random sampling, with data collection using questionnaires and partial least square (pls) analysis. The results of the study show that training has a significant effect on the productivity of MSMEs, both directly and through strengthening social capital, where trust, norms, networks, and mutual relationships play a role in strengthening the impact of training. This study shows that increasing the productivity of MSMEs is not enough only through technical training, but needs to be integrated with efforts to strengthen social capital so that business actors are able to optimize production, marketing, and technology processes in a sustainable manner.